Zakat Wakalah system in Malaysia: An extension of innovation diffusion theory - Hanudin Amin (Emerald Insight, 2024)
This study aims to evaluate drivers that explain the acceptance of the zakat Wakalah (ZW) system in Malaysia. Design/methodology/approach – Innovation diffusion theory (IDT) was tested to examine 441 zakat payers’ willingness to perform the ZW system using SmartPLS4.0. Findings – All factors sourced from the IDT, including gender, were significantly related to the acceptance of the ZW system. Research limitations/implications – The generalization of the outcomes generated was limited to the geography concerned and the confined exogenous variables. Practical implications – By focusing on the key attributes of the IDT and the gender role, zakat institutions can enhance the system’s appeal, improve its adoption rates and ensure that it is effectively meeting the needs of the community. Originality/value – This study introduced a modified IDT called ZW–IDT framework to Analyse its adoption, scalability and impact on zakat distribution effectiveness.